The impact of cyber-attacks on companies and organisations in developed countries - Kazim, Ali Khalid Diwan; Shanshul, Nisreen Riad (Edelweiss Applied Science and Technology, 2024)
Cyber-attacks are a growing threat to businesses and organisations in developed countries. They bring about significant financial losses, operational disruptions, and a decline in customer confidence. It is estimated that cybercrime could run up the global economy to $10.5 trillion annually by 2025 in comparison to $3 trillion in 2015. For example, British companies ran into losses estimated at $55 billion during 2018–2023 as a result of these attacks. These attacks go after vital sectors such as financial services, energy, and healthcare. They disrupt daily operations and bring on direct and indirect financial losses. In addition, the loss of sensitive data can bring down corporate reputation and lower customer and investor confidence. To deal with these challenges, it has become necessary to step up cybersecurity investments and work out sophisticated defence strategies.